Hubungan Antara Tingkat Kecemasan, Pola Makan, dan Indeks Massa Tubuh (IMT) Terhadap Gangguan Siklus Menstruasi pada Remaja Putri Kelas 12 di SMAN 1 Praya - Syakira Ziad; Ida Ayu Made Mahayani; Wendy Handayani; Lalu Yogi Prasetio Imam (Jurnal Pengabdian Ilmu Kesehatan, 2026)
Menstrual cycle disorders are a reproductive health problem frequently experienced by adolescent girls and are influenced by psychological factors and nutritional status. This study aims to analyze the relationship between anxiety levels, diet, and body mass index (BMI) with menstrual cycle disorders in 12th-grade female adolescents at SMAN 1 Praya. The study used a cross-sectional design with 183 respondents selected by purposive sampling. Data were collected through the DASS-21 (Anxiety Spectrum) questionnaire, FFQ (Food Frequency Questionnaire), anthropometric measurements, and menstrual cycle questionnaires, then analyzed using the Spearman Rank test (α = 0.05). The results showed that 37.2% of respondents experienced menstrual cycle disorders. There was a significant relationship between anxiety (rs = 0.420; PR = 2.31), diet (rs = −0.395; PR = 2.80), and BMI (rs = 0.188; PR = 2.20) with menstrual cycle disorders (p < 0.05). It was concluded that anxiety, diet, and BMI play a role as risk factors for menstrual cycle disorders in adolescent girls, so that promotive interventions are needed through mental health education, nutritional improvement, and monitoring of nutritional status in schools.